KAJIAN KREDIBILTAS PROFESI JAKSA SEBAGAI PENEGAK HUKUM TERHADAP MASYARAKAT MENENGAH KE BAWAH - Saly, Jeane neltje; The, Chelsea; Mayvians, Tidelstein; Okhram, Bukhari; Pitang, Govara Remeina (Peneliti.net, 2023)
Criminal prosecution is a business process for the confirmation or actual control of legal norms in traffic or legal relations in social and national life. People in social life basically have certain ideas about what is good and what is bad. Through the use of prescriptive research methods, i.e. processes that explore jurisprudence, jurisprudence and jurisprudence to answer legal questions. In striving to be a principled and responsible country in which the rule of law prevails, the role and functioning of the judiciary, which is free, independent and free from the influence of power, including political parties, is very important as it aims to ensure justice. is important. and discipline. and disciplined justice. rule of law society. The Attorney General's Code of Ethics constitutes the basic standards and serves as a reference for defining the boundaries of the agency's field of activity. A prosecutor's code of ethics is a set of documented, codified (ordered in a systematic way) moral principles